Money demand and financial liberalization : revisting divisia money in Malaysia - Lee, Wen Wen. (Universiti Malaysia Sarawak (UNIMAS), 2007)
Financial liberalization and innovation that have emerged in Malaysia since the late 1970s has been alleged to cause the breakdown in the previously stable money demand function,which in line has impeded the usefulness of monetary targeting based on simple-sum aggregation method. Barnett (1980) proposed Divisia monetary aggregation as to contrast with the conventional simple-sum aggregation. Covering the period of 1981:Q1 to 2004:Q4, we reexamine the effects of financial liberalization and innovation on money demand functions, using the conventional simple-sum and Divisia monetary aggregates (of M1 and M2). Also, we test the relative performances these aggregates and investigate the relationship between money demand with income, interest rate and exchange rate. By applying cointegration, error-correction model and Granger - causality tests, results indicated that Divisia M2 has the best properties among all of the aggregates. Given its superiority theoretically and empirically, we strongly advocate the use of Divisia monetary aggregates in the course of monetary targeting, and subsequently, in the conduct of monetary policy.